Population Pharmacokinetics and Pharmacogenetics Analysis of Rilpivirine in HIV-1-Infected Individuals - Aouri, Manel (Antimicrob Agents Chemother, 2016)
Rilpivirine (RPV), the latest nonnucleoside reverse transcriptase inhibitor active against HIV-1, is prescribed in a standard dosage of 25 mg once a day in combination with emtricitabine (FTC) and tenofovir disoproxil fumarate (TDF). The aim of this observational study was to characterize the RPV pharmacokinetic profile, to quantify interpatient variability, and to identify potential factors that could influence drug exposure. RPV concentration data were collected from HIV-infected patients as part of routine therapeutic drug monitoring performed in our center (Laboratory of Clinical Pharmacology). A population pharmacokinetic analysis was performed with NONMEM by comparing various structural models. The influence of demographic and clinical covariates, as well as frequent genetic polymorphisms in 5 genes (CYP3A4*22, CYP3A5*3, CYP2C19*2, CYP2C19*17, UGT1A1*28, and UGT1A4*2), on RPV elimination was explored. A total of 325 plasma concentration measurements were obtained from 249 HIV-positive patients. Plasma concentrations ranged from 12 to 255 ng/ml. A one-compartment model with zero-order absorption best characterized RPV pharmacokinetics. The average RPV clearance (CL) was 11.7 liters/h, the average volume of distribution was 401 liters, and the mean absorption time was 4 h. The interinterindividual variability (IIV) for CL was estimated to be 33%. None of the available demographic or genetic covariates showed any influence on RPV pharmacokinetics, but 29% of the patients were predicted to present minimal concentrations below the recently identified target cutoff value of 50 ng/ml. The variability in RPV pharmacokinetics appears to be lower than that for most other antiretroviral drugs. However, under the standard regimen of 25 mg daily, a significant number of patients might be underdosed. It remains to be investigated whether the underexposure has an impact on the development of resistance while patients are on maintenance therapy.